Penguatan Karakter Religius Siswa melalui Pembiasaan di UPT SD Negeri 119 Gresik - Putri Permata Ali; Ismail Marzuki (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Strengthening Students' Religious Character Through Habituation at UPT SD Negeri 119 Gresik.The research object is aimed at children aged 7-8 years. This research uses the case study method, which is a form of qualitative research that uses human understanding and behavior based on human opinion. Data collection techniques through observation, interviews and documentation. The results of the research I conducted show that the role of the teacher in the process of learning manners in everyday life is very important for children aged 7-8 years because the teacher plays the role of role model, observer, supporter, facilitator, evaluator. This research activity has concluded an understanding regarding simple etiquette in eating times must be emphasized in the school environment so that students become polite and ethical children, therefore teachers have an important role in learning etiquette in the school environment and are able to be wise role models for their students.